Environmental impact changes in the southern region of colombia before and after the peace accords agreements made in 2016, between Colombia's government and the FARC's guerrilla, applying remote sensing with landsat 8 and sentinel 2 satellite images (2020)
A multi-temporal study using satellite images from Landsat 8 and Sentinel 2 was done to analyse the land cover uses in the departments of Cauca, Nariño and Putumayo. These analysis were done by using supervised classifications, with the Focus software of the Geomatica program, of images dating from 2015 up to the latest available. The main objective was to compare the environmental impact changes that the 2016 peace agreements had in terms of deforestation due to illegal crops and mining, for example. Results varied depending of the region of study and the presence of unwanted interference in the data, mainly the cloud and shadow land cover percentages. Despite this, some clear tendencies were seen regarding the increase in deforestation on nearby urban settlements and riverbeds, due to the increase of crops and soil land cover. These changes partially were explained because of the rising of other criminal groups, that took advantage of the decreasing influence of FARC in key areas and the lack of control of the authorities, to further the environmental damage. Also, the lack of sustainable strategies to eradicate illegal crops using toxic chemicals, affected both foreign and native fauna thus heavily increasing the environmental impact on key areas. Finally, excessively strict legislation regarding the legal exploitation on natural resources in protected territories, implied that illegal groups were the ones that dominated the extraction process without caring for the environment and its long-term consequences, given the absence of the Government to enforce the law in these territories.